THE EFFECTIVENESS OF AN ANDROID-BASED NUMBER LEARNING GAME APPLICATION ON ELEMENTARY SCHOOL STUDENTS' NUMERACY SKILLS - Saleh, Lukman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study investigates the effectiveness of an Android-based number learning game application in enhancing the numeracy skills of elementary school students at SD Negeri 74 Ambon. Using a pre-experimental design with a one-group pretest-posttest format, a total of 60 students from grades IV, V, and VI participated. Data were collected through a numeracy skills assessment administered before and after the intervention. The results indicate a significant improvement in the students' numeracy skills, with average scores increasing from 62.10 in the pretest to 82.05 in the posttest, yielding a mean N-Gain of 0.53, categorized as moderate. These findings suggest that the integration of engaging digital game-based learning significantly contributes to students' understanding and application of numerical concepts. The study highlights the potential of utilizing educational technology to foster an interactive learning environment conducive to enhancing student learning outcomes.